2019
DOI: 10.1051/0004-6361/201936239
|View full text |Cite
|
Sign up to set email alerts
|

Gas shells and magnetic fields in the Orion-Eridanus superbubble

Abstract: Aims. The Orion-Eridanus superbubble has been blown by supernovae and supersonic winds of the massive stars in the Orion OB associations. It is the nearest site at which stellar feedback on the interstellar medium that surrounds young massive clusters can be studied. The formation history and current structure of the superbubble are still poorly understood, however. It has been pointed out that the picture of a single expanding object should be replaced by a combination of nested shells that are superimposed a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 55 publications
2
33
0
Order By: Relevance
“…The idea that the Orion clouds were and are being affected by the feedback of massive stars is not new (e.g., Bally et al 1987;Bally 2008). It has been proposed that several nested shells are superimposed along the line-of-sight, forming the so called Orion-Eridanus superbubble, a less than 10 Myr old relic shell of several Supernovae remnants, spatially encircling the main Orion clouds (e.g., Lee & Chen 2009;Pon et al 2014bPon et al ,a, 2016Ochsendorf et al 2015;Soler et al 2018;Joubaud et al 2019). The progenitors of the superbubble are likely related, at least partially, with the Orion−6 event presented in this paper.…”
Section: Coherent Radial Cloud Motions In Orion On the 100 Pc Scalementioning
confidence: 69%
See 1 more Smart Citation
“…The idea that the Orion clouds were and are being affected by the feedback of massive stars is not new (e.g., Bally et al 1987;Bally 2008). It has been proposed that several nested shells are superimposed along the line-of-sight, forming the so called Orion-Eridanus superbubble, a less than 10 Myr old relic shell of several Supernovae remnants, spatially encircling the main Orion clouds (e.g., Lee & Chen 2009;Pon et al 2014bPon et al ,a, 2016Ochsendorf et al 2015;Soler et al 2018;Joubaud et al 2019). The progenitors of the superbubble are likely related, at least partially, with the Orion−6 event presented in this paper.…”
Section: Coherent Radial Cloud Motions In Orion On the 100 Pc Scalementioning
confidence: 69%
“…However, a clear determination of such a central point of origin is not straightforward due to different reasons: (a) There is likely not a single point of origin in the first place. Several massive stars formed in the region and produced feedback (radiation, SNe, winds), as indicated by the nested shells in the Orion-Eridanus superbubble (Ochsendorf et al 2015;Joubaud et al 2019, see also the Discussion in Sect. 5.2).…”
Section: Relative Space Motions Of Molecular Clouds In Orionmentioning
confidence: 95%
“…(Dawson et al 2015) have shown a strong association between molecular gas formation and superbubbles. Close-by molecular clouds in the Gould Belt -at a distance from the Sun of d < 500 pc -such as Orion (Soler et al 2018;Joubaud et al 2019;Könyves et al 2020), Taurus, Perseus (Shimajiri et al 2019), and Ophiuchus (Ladjelate et al 2020), were also found to be shaped by large-scale compression from expanding shells and bubbles in their magnetized surroundings.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, CR that are produced internally can remain confined in the superbubble medium for typically 300 kyr for 100 GeV particles in a 25-50 pc superbubble if the diffusion lengths are 100 times shorter than in the Article number, page 1 of 20 arXiv:2001.10139v1 [astro-ph.HE] 28 Jan 2020 the key H α features towards Orion. In the analysis region, the black contours delineate the main H i shells related to the superbubble, i.e the North Rim (N), South Loop (S), East Shell (E), and West Rim (W), and the Eridu cirrus (C) lying outside the superbubble (Joubaud et al 2019). The molecular MBM 20 cloud in front of the superbubble edge is outlined in white.…”
Section: Introductionmentioning
confidence: 99%